Mediating role of resilience in the relationships of social capital, commitment and career success of entrepreneurs in Nigeria - Isyaku, Salisu (2018)
Although the positive relationships among social capital, commitment, and career success were well documented, however, there were relatively few studies relating these variables in developing economies, and especially in Nigeria. Additionally, how resilience actually shapes the relationships between social capital (bonding and bridging), commitment and career success of entrepreneurs is somehow neglected. Therefore, the central objective of this study is to examine the mediating role of resilience in the relationships of social capital (bonding and bridging), commitment and career success of entrepreneurs in Nigeria. The study drew from the conservation of resources, broaden-and-build, and social capital theories to explain these relationships. The study gathered data from 390 entrepreneurs in Nigeria by crosssectional approach. The study used two-stage cluster sampling approach to select the required clusters and simple random sampling to select the final samples from the total population. The questionnaires were distributed and collected through selfadministered technique. The hypotheses were tested using Partial Least Square Structural Equation Modelling statistical software (Smart-PLS 3). The findings revealed that bonding, commitment as well as resilience were significant and positive predictors of career success of entrepreneurs. Also, resilience significantly intervened in the relationships between bonding social capital and career success and between commitment and career success. The outcomes of this study deliver essential insights to entrepreneurs, researchers as well as policy makers to further understand the effects of social capital, commitment and resilience on career success. The findings suggested that for entrepreneurs to be successful in their career, they need to have a good connection with their immediate people, group and community and be committed toward achieving their career. More importantly, the results revealed the need for them to be resilient due to the turbulent nature of their environment. Theoretical, methodological and practical implications were also discussed.